3D FE modeling and experimental analysis of residual stresses and machining characteristics induced by dry, MQL, and wet turning of AA6061-T6. Issue 6 (28th October 2021) - Javidikia, Mahshad; Sadeghifar, Morteza; Songmene, Victor; Jahazi, Mohammad
Abstract: The present research study aimed to investigate the influences of turning environments and parameters on machining temperature (MT), machining forces (MFs), and axial surface residual stresses (ASRS) in turning operation of AA6061-T6. Turning environments included DRY, minimum quantity lubrication (MQL), and WET modes, and turning parameters consisted of cutting speed ( V ), feed rate ( f ), depth of cut ( D ), tool nose radius ( r ), side cutting edge angle (SCEA), and back rake angle (BRA). A 3D finite element (FE) model was developed to predict MT, MFs, and ASRS for different turning environments and parameters and was validated by experimental measurements. The results showed that increasing feed rate led to a higher tensile ASRS while using tools with a nose radius of 0.4 mm resulted in lower ASRS. In addition, the deviation of SCEA from 0° to positive or negative values caused higher tensile ASRS. ASRS increased with decreasing BRA from 0° to –15°. The variation of ASRS was found to be more sensitive to thermal effects than to mechanical ones. The results further confirmed that in a turning process, the competition between the machining forces and temperature was the fundamental factor that determined the extent of residual stresses.